Strategy for Developing the Arabic Environment at Madrasah Tsanawiyah Negeri (MTsN) 3 Malang : Strategi Pengembangan Lingkungan Bahasa Arab di Madrasah Tsanawiyah Negeri (MTsN) 3 Malang - M. Ibnu Ahmad; Arif Mustofa; Muh. Faruq; Syafiyatul Maf'udah; Eva Fauziyyah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Learning Arabic in a madrasah requires special conditions to enrich the active language experience. More is needed in a conventional classroom, and an environment that supports the Arabic learning process is also needed. This paper aims to describe the role of the language environment in Arabic language learning, the strategic steps of MTsN 3 Malang in developing Arabic language environment development programs, and their impact on language learning. This research uses qualitative research methods with a case study approach. This approach was chosen because it aligns with the research objective to gain an in-depth understanding of the strategies for developing the Arabic language environment at Madrasah Tsanawiyah Negeri (MTsN) 3 Malang. The results show that the development of the Arabic language environment at MTsN 3 Malang is carried out in three strategic steps, namely 1) the formation of Arabic language drivers, 2) the installation of Arabic language zones, and 3) the socialization and reinforcement of Arabic language competencies for teachers. These strategic steps have an impact on 1) improving students' Arabic language skills, 2) improving the competence and quality of teachers, 3) using innovative teaching methods, 4) forming an Islamic learning environment, 5) strengthening students' religious identity in the MTsN 3 Malang environment. Keywords: Arabic Environment, Arabic Acquisition, Madrasah Tsanawiyah.